The Global Status of Research in Ankle Fracture: A Bibliometric and Visualized Study - Zeng, Jianshuang; Xu, Cheng; Xu, Gaoxiang; Wang, Daofeng; Zhang, Wupeng; Li, Hua; Gan, Xuewen; Xiong, Ying; Li, Jiantao; Zhang, Licheng; Tang, Peifu (Frontiers in Surgery, 2022)
Background Ankle fractures are common lower extremity fractures that pose a significant economic and social burden. This study analyzed the ankle fracture research literature between 2000 and 2021 to clarify the current status of ankle fracture research and predict future research trends. Methods Publications related to ankle fractures published between 2000 and 2021 were retrieved from the Web of Science Core Collection. Then Bibliometric analysis and Visualized Study were performed by VOSviewer software. Results A total of 2656 publications were retrieved. The number of publications related to ankle fractures is increasing every year. The top countries and journals in terms of the total number of publications, number of citations, and H-index ranking were USA and foot and ankle int. Lorich DG had the most publications in this field. University of Amsterdam's research group had the biggest number of publications in this field. Co-occurrence analysis clustered the keywords into seven clusters: survival analysis and prognosis study, internal fixation treatment study, treatment study of combined deltoid ligament rupture, treatment study of combined inferior tibiofibular ligament injury, treatment study of posterior ankle fracture, treatment study of postoperative traumatic arthritis of ankle fracture, and treatment study of ankle injury in children. Conclusions The importance of ankle fractures is increasing year by year with the aging process, and the number of publications related to ankle fractures will not continue to increase in the future. Survival and prognosis studies, internal fixation studies, combined deltoid ligament rupture studies, and combined inferior tibiofibular ligament injury studies may become the future research hotspots in the field of ankle fractures.